THE COMPENSATION POLICY FOR NON-PERMANENT EMPLOYEES DURING THE PANDEMIC TOURISM SERVICE OF BOALEMO DISTRICT - rikriyanto neno; azis rachman; maman musa (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This research aims to find out the compensation policy for temporary employees during the pandemic of the Boalemo Regency Tourism Office. This research is descriptive qualitative. The data collection techniques used in this research was observation, in-depth interviews, and documentation. The research results showed that financial compensation was very influential on non-permanent employees at the Tourism Office, both from salaries, incentives, bonuses, and allowances; it was clear from the current pandemic conditions. Based on the results obtained, some policies needed to be considered by local governments. As well as the Tourism Office providing financial compensation, including incentives and bonuses, there was no budget for the two types of compensation provided by the Tourism Office to non-permanent employees and ASN. Meanwhile, non-financial compensation also influenced work motivation for all employees in the Tourism Office, non-financial compensation for employees such as providing facilities and a comfortable work environment.